Disparate patterns of thermal adaptation between life stages in temperate vs. tropical Drosophila melanogaster. (16th January 2018) - Lockwood, B. L.; Gupta, T.; Scavotto, R.
Abstract: Many terrestrial ectothermic species exhibit limited variation in upper thermal tolerance across latitude. However, these trends may not signify limited adaptive capacity to increase thermal tolerance in the face of climate change. Instead, thermal tolerance may be similar among populations because behavioural thermoregulation by mobile organisms or life stages may buffer natural selection for thermal tolerance. We compared thermal tolerance of adults and embryos among natural populations of Drosophila melanogaster from a broad range of thermal habitats around the globe to assess natural variation of thermal tolerance in mobile vs. immobile life stages. We found no variation among populations in adult thermal tolerance, but embryonic thermal tolerance was higher in tropical strains than in temperate strains. We further report that embryos live closer to their upper thermal limits than adults – that is, thermal safety margins are smaller for embryos than adults. F1 hybrid embryos from crosses between temperate and tropical populations had thermal tolerance that matched that of tropical embryos, suggesting the dominance of heat‐tolerant alleles. Together, our findings suggest that thermal selection has led to divergence in embryonic thermal tolerance but that selection for divergent thermal tolerance may be limited in adults. Further, our results suggest that thermal traits should be measured across life stages to better predict adaptive limits.